Pentingnya Pengelolaan Kelas Dalam Pembelajaran - Tibta Ilmiahwati; Sukma Wijayanto (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Class management is needed because the behaviour and actions of students every day andevery time will change often. It is possible that today students can study ip peace, buttomorrow is not necessarily . The class is always dynamic with the form of behaviour,actions, attitudes, mental, and emotional children.Professional teachers are teachers whoare able to manage the class well. In the classroom, all aspects of teaching and learningmeet and process. Teachers with all their abilities, and students with all their backgroundsand individual characteristics, the curriculum with its components, learning materialsand resources with the subject matter meet and integrate in the classroom. The result ofeducation and teaching are largely determined by what happens in the classroom. For that,the class should be managed professionally.